Technical information capture for food product innovation in Thailand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University in Food Technology at Massey University, Palmerston North, New Zealand - Prasong Siriwongwilaichat (Massey University, 2001)
Since rapidly effective product design and launch requires advanced technical skills and as new knowledge is expanding at an exponential rate, it is critical that food technologists keep up to date with international scientific developments. This is significant in Thailand in which the food market has been developed as a result of greater industrialisation, changes in consumer lifestyle and higher demand for processed foods. This study has identified the main technical knowledge sources used by Thai food manufacturing companies to support their development of new branded food products. Data were obtained from interviews with sixty two food processing companies, forty three potential providers of technical information and services, and from three focus groups held with technical food product developers. Internal technical staff in the food manufacturing companies were the major source of technical knowledge for food product development. Food ingredient suppliers were the most important outside providers of knowledge to these technical staff. The main technical information and services provided by the food ingredient suppliers included ingredient specifications, food recipes, consultancy, and product testing. Technical information was mostly required to support product formulations, food processing, shelf life studies, and quality control. New products that were radically innovative required more external technical knowledge sources, usually equipment suppliers, than those that were incrementally innovative. The main barriers to technical knowledge absorption were foreign language difficulties, time limitation and business secrecy. To strengthen food product development activities in Thailand, it is recommended that a company enhance internal technical staff's capabilities to absorb external technical knowledge more efficiently. In addition, the technical knowledge providers should also simplify technical information access to the food companies.
Keywords: Food industry and trade; Food technology; Technological innovations; New products; Thailand; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290103 Food processing